Association between mortality and cardiovascular diseases in the vulnerable Mexican population: A cross-sectional retrospective study of the COVID-19 pandemic - Gerardo R. Padilla-Rivas; Juan Luis Delgado-Gallegos; Gerardo Garza-Treviño; Kame A. Galan-Huerta; Zuca G-Buentello; Jorge A. Roacho-Pérez; Michelle Giovana Santoyo-Suarez; Hector Franco-Villareal; Ahidée Leyva-Lopez; Ana E. Estrada-Rodriguez; Jorge E. Moreno-Cuevas; Javier Ramos-Jimenez; et al. (Frontiers Media S.A., 2022)
Cardiovascular diseases (CVDs) continue to be the leading cause of death worldwide. Over the past couple of years and with the surge of the COVID-19 pandemic, mortality from CVDs has been slightly overshadowed by those due to COVID-19, although it was during the peak of the pandemic. In the present study, patients with CVDs (CVDs; n = 41,883) were analyzed to determine which comorbidities had the largest impact on overall patient mortality due to their association with both diseases (n = 3,637). Obesity, hypertension, and diabetes worsen health in patients diagnosed positive for COVID-19. Hence, they were included in the overview of all patients with CVD. Our findings showed that 1,697 deaths were attributable to diabetes (p < 0.001) and 987 deaths to obesity (p < 0.001). Lastly, 2,499 deaths were attributable to hypertension (p < 0.001). Using logistic regression modeling, we found that diabetes (OR: 1.744, p < 0.001) and hypertension (OR: 2.179, p < 0.001) significantly affected the mortality rate of patients. Hence, having a CVD diagnosis, with hypertension and/or diabetes, seems to increase the likelihood of complications, leading to death in patients diagnosed positive for COVID-19.